Thermoelastic Properties of Liquid Fe‐Rich Alloys Under Martian Core Conditions - D. Huang; Y. Li; Khan, A; Sossi, P.; Giardini, D; Murakami, M. (Geophysical Research Letters, 2023)
Seismic measurements made on Mars indicate that the liquid iron‐nickel core is rich in light elements; however, the effects of these light components on the elasticity of Mars' core remain poorly constrained. Here, we calculate elastic properties of various liquid Fe‐X (X = Ni, S, C, O and H) mixtures using ab initio molecular dynamics simulations. We find that, at martian core conditions, the addition of S and O most effectively decreases the density of liquid iron, followed by C and H, while Ni has a minimal effect. As for compressional sound velocity (Vp), C increases Vp of liquid Fe throughout Mars' core, while both S and O reduce Vp, the intensity of which diminishes with increasing pressure. Assuming a martian core made of a binary mixture, the seismically‐inferred density would require the presence of at least 30 wt% S.